Antibacterial potentiality of Argemone mexicana solvent extracts against some pathogenic bacteria - Indranil Bhattacharjee; Soroj Kumar Chatterjee; Soumendranath Chatterjee; Goutam Chandra (Memorias do Instituto Oswaldo Cruz, 2006)
The sensitivity of two Gram positive (Staphylococcus aureus and Bacillus subtilis) and two Gram negative (Escherichia coli and Pseudomonas aeruginosa) pathogenic multi-drug resistant bacteria was tested against the crude extracts (cold aqueous, hot aqueous, and methanol extracts) of leaves and seeds of Argemone mexicana L. (Papaveraceae) by agar well diffusion method. Though all the extracts were found effective, yet the methanol extract showed maximum inhibition against the test microorganisms followed by hot aqueous extract and cold aqueous extract.